Antibacterial activity of ethanolic extract and fractions of Piper betle L. (Fam. Piperaceae) - Banzuela, Josette Karen B.; Cahilig, Anne Nicole O.; Luz, Regina Beatriz C.; Ladignon, Ethel Andrea C. (​​​​​​​​​​Manila: Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
Recent studies on Piper betle L. have reported it to exhibit antibacterial activity against a broad range of species, including Gram-positive and Gram-negative ones. The study mainly aimed to profile Piper betle L. found in the Philippines through fractionation of its ethanolic leaf extract, as well as characterization and identification of its components. It was subjected to cold maceration using 70% ethanol. Pharmacopeial tests (foreign matter, loss on drying, total ash content, and total extractives tests) were then performed on the extract. It was subjected to liquid-liquid partitioning, obtaining hexane, dichloromethane, ethyl acetate, and water fractions. The fraction and extract solutions were subjected to phytochemical tests, thin-layer chromatography, and antibacterial screening. The samples were found to have passed all pharmacopeial tests, based on criteria from Philippine Pharmacopeia 1. The antibacterial activities of the solutions were evaluated through measurement of their zones of inhibition against Pseudomonas aeruginosa and Staphylococcus aureus, in which the only significant activity was that of hexane fraction against P. aeruginosa, having an inhibition zone of 1.6±0.53 cm. The water fraction obtained the highest yield (43.51%), but it did not elicit significant antibacterial activity. Results showed that the crude extract possessed saponins, steroids, tannins and phenols, alkaloids, carbohydrates, and fixed oils, while the fractions varied in their possession of the aforementioned constituents. It was concluded that the extract was effectively fractionated, and the solutions successfully characterized. The solution with the most significant antibacterial activity was also identified.
Available to the general public.
​​​​​​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines Manila, June 2017.
Keywords: Piper betle; Plant extracts; Piperaceae